2021
DOI: 10.21608/eajbsa.2021.196735
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Saponins Extracted from Yucca schidigera Roezl against the Major Storage Pest, Tribolium castaneum (Herbst)

Abstract: http://eajbsa.journals.ekb.eg/ Efficacy of Saponins Extracted from Yucca schidigera Roezl against the Major Storage Pest, Tribolium castaneum (Herbst)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The results in this study showed that Yucca schidgera extract was effective for the control of red flour beetle in relation to mortality of adults and offspring inhibition. The insecticidal activity of Y. schidgera extract against T. castaneum may be attributed to the presence of saponins known to have a toxic effect against this insect (Bakr and Gad 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study showed that Yucca schidgera extract was effective for the control of red flour beetle in relation to mortality of adults and offspring inhibition. The insecticidal activity of Y. schidgera extract against T. castaneum may be attributed to the presence of saponins known to have a toxic effect against this insect (Bakr and Gad 2021).…”
Section: Discussionmentioning
confidence: 99%